Simple and efficient design towards a significant improvement of the optical absorption of amorphous silicon solar cell. (November 2021) - Elsayed, Hussein A.; Sayed, Hassan; Taha, T.A.; Alharbi, Abdullah G.; Alenad, Asma M.; Alshammari, Basheer A.; Ahmed, Ashour M.; Mehaney, Ahmed; Aly, Arafa H.
Highlights: The present work introduce a simple and efficient design towards a prominent enhancement of the optical characteristics of amorphous silicon solar cells. We have theoretically demonstrated the role of the one dimensional photonic crystals as an anti-reflecting coating and back reflector to improve the absorption properties of the proposed cell. The anti-reflecting coating is designed from a single period of the one dimensional quadrant photonic crystals. Whilst, 10 periods of the one dimensional binary photonic crystals are used to design the back reflecting mirror. The investigated results verify a significant increase in the absorption values of the cell to 0.97 in the wavelengths domain from 400 nm to 640 nm. Abstract: In recent times, solar cell presents a good candidate for solving the problems of energy crisis and environmental pollution as well. However, it could suffer from the limited absorption among the full spectral wavelength. In this context, we present in this paper a simple and efficient design towards a prominent enhancement of the optical characteristics of amorphous silicon solar cells. Here, we have theoretically demonstrated the role of the one-dimensional photonic crystals as an anti-reflecting coating and back reflector to improve the absorption properties of the proposed cell. The anti-reflecting coating is designed from a single period of the one-dimensional quadrant photonic crystals. Whilst 10 periods of the one dimensional binary photonic crystals are used to design the back reflecting mirror. The theoretical framework of our study is mainly based on the finite element method and the transfer matrix method as well. The investigated results verify the significant role of the anti-reflecting coating and the back mirror in raising the absorption values of the cell that could reach over than 0.9 in the wavelength domain from 350 nm to 640 nm. Moreover, the change in the values of the angle of incidence investigates a distinct decrease in spectral absorption.